Removal of VOCs by catalytic process. A study of MnZnO composites synthesized from waste alkaline and Zn/C batteries - Gallegos, María Victoria (2017)
Spent alkaline and zinc-carbon batteries were subjected to a biohydrometallurgy process, in order to recover manganese and mixed manganese zinc oxides. Two solids were synthesized, one of them prepared by reaction of MnSO4 and KMnO4 (MnOx) and the other obtained by chemical precipitation with NaOH (ZnMnO). The characterization by XRD, TPR, FTIR and XPS revealed the presence of Mn3+ and Mn4+ cations in both samples, and the presence of ZnO and Mn-Zn spinels in ZnMnO. The samples were evaluated in the oxidation reaction of ethanol and toluene. The results in the flow reactor showed that ethanol conversion on both catalysts, MnOx and ZnMnO, is rather similar, but toluene conversion is markedly higher on MnOx, due to a greater Mn/Zn ratio and to the absence of a crystallized ZnO phase. The FTIR study demonstrated that ethanol is oxidized to acetaldehyde at low temperature, and to CO2 and CO at 400 C. Traces of CH4 in the gas phase are also detected at high temperature. The formation of ethoxy and acetate groups is observed at the catalyst surface. With respect to toluene oxidation, CO2 is detected at 300 C and when the temperature is increased, CO is also observed in the gas phase. The results showed that: (i) the alkaline and Zn-carbon batteries can be recycled as catalysts and (ii) the solids can be used in the catalytic process for VOCs control.